How To Reach Intense Luminescence for Compounds Capable of Excited‐State Intramolecular Proton Transfer?. Issue 22 (9th April 2016) - Skonieczny, Kamil; Yoo, Jaeduk; Larsen, Jillian M.; Espinoza, Eli M.; Barbasiewicz, Michał; Vullev, Valentine I.; Lee, Chang‐Hee; Gryko, Daniel T.
Abstract: Photoinduced intramolecular direct arylation allows structurally unique compounds containing phenanthro[9′, 10′:4, 5]imidazo[1, 2‐ f ]phenanthridine and imidazo[1, 2‐ f ]phenanthridine skeletons, which mediate excited‐state intramolecular proton transfer (ESIPT), to be efficiently synthesized. The developed polycyclic aromatics demonstrate that the combination of five‐membered ring structures with a rigid arrangement between a proton donor and a proton acceptor provides a means for attaining large fluorescence quantum yields, exceeding 0.5, even in protic solvents. Steady‐state and time‐resolved UV/Vis spectroscopy reveals that, upon photoexcitation, the prepared protic heteroaromatics undergo ESIPT, converting them efficiently into their excited‐state keto tautomers, which have lifetimes ranging from about 5 to 10 ns. The rigidity of their structures, which suppresses nonradiative decay pathways, is believed to be the underlying reason for the nanosecond lifetimes of these singlet excited states and the observed high fluorescence quantum yields. Hydrogen bonding with protic solvents does not interfere with the excited‐state dynamics and, as a result, there is no difference between the occurrences of ESIPT processes in MeOH versus cyclohexane. Acidic media has a more dramatic effect on suppressing ESIPT by protonating the proton acceptor. As a result, in the presence of an acid, a larger proportion of the fluorescence of ESIPT‐capable compounds originates from their enol excited states. Abstract : Changing states : UV‐mediated intramolecular direct arylation affords rigid excited‐state intramolecular proton transfer (ESIPT)‐capable heterocycles with tunable fluorescent properties. A small dihedral angle prevents deactivation of the excited state after ESIPT, and the introduction of a 3‐hydroxypyridine moiety further modulates the photophysical properties by altering the relative population of enol and keto excited states in protic solvents (see figure).